Qualitative Research in Counselling and Psychotherapy - Mcleod John (Sage Publications, 2001)
This book has been written to help Researchers find their way through the range of Methodologies and Techniques available to them. Preface ,Qualitative Inquiry and the Reconstruction of Counselling and Psychotherapy, The Relevance and Contribution of Hermeneutics, The Phenomenological Approach, Hermeneutics and Phenomenology: the Core of Qualitative Method, Ethnographic Approaches to Research in Counselling and Psychotherapy, Using Grounded Theory, The Analysis of Conversation and Discourse and Narrative, Qualitative Inquiry as Bricolage, How to Do Qualitative Research, The Role of Qualitative Methods in Outcome Research, Critical Issues in the Use of Qualitative Inquiry, References, Index.